Pelatihan Pengembangan Media Pembelajaran Berbasis Digital - Sari, Tri Maya; Mahardini, Angger Putri (Al Mufid, 2024)
Digital-based media is a productive activity that is related to the teacher's skills process in developing and implementing digital-based learning media. This PKM aims to increase teachers' knowledge and skills in terms of implementing digital-based learning media. This service is carried out using pre-implementation, implementation and post-implementation methods. The results of this PKM activity show that the process of implementing digital-based learning media is smooth